The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1089/jmf.2008.0219
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of the Oil from the Fruit ofBlighia sapidaand Toxicological Evaluation of the Oil-Based Diet in Wistar Rats

Abstract: The physicochemical properties of the oil from the fruit of Blighia sapida and the toxicological effect of the oil-based diet on some biochemical parameters of selected rat tissues and serum were studied. The smoke, flash, and fire points as well as peroxide, iodine, and acid values of the fruit oil were significantly lower (P < .05), whereas the specific gravity, relative density, saponification, and ester values compared well with soybean oil. The fruit oil yield was 20.02%. The oil consisted of 22.22% satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
12
1
2
Order By: Relevance
“…B. sapida (Ackee) a known fish poison and the hypoglycin A and B have been identified as the toxicant in the seed (Bowen-Forbes and Minott, 2009;Moya, 2001;Natalini et al, 2000). The fruit is rich in essential fatty acids, vitamin A, zinc, and protein (Oladiji et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…B. sapida (Ackee) a known fish poison and the hypoglycin A and B have been identified as the toxicant in the seed (Bowen-Forbes and Minott, 2009;Moya, 2001;Natalini et al, 2000). The fruit is rich in essential fatty acids, vitamin A, zinc, and protein (Oladiji et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…4.3b ) (Emanuel and Benkeblia, unpublished data). Oladiji et al (2009) analyzed the physicochemical properties of the oil from ackee fruit. They found that the fruit oil yield was 20.02%, and consisted of 22.22% saturated, 56.43% monounsaturated, and 21.35% polyunsaturated fatty acids.…”
Section: Biochemical Compositionmentioning
confidence: 99%
“…A se sujet, une étude très récente menée au Nigeria donne les proportions d'acides gras présentes dans l'huile extraite de l'arille de BHS suivante : 22,22% d'acides gras saturés, 56,43% d'acides gras monoinsaturés et 21,35% d'acides gras polyinsaturés. Cette huile selon Oladiji et al (2009) est plus riche en acides béhéniques, palmitoléiques, oléiques, gadoléiques, éruciques et 9, 12 éicosanoique que l'huile de soja. Le pourcentage d'élévation de ces gras par rapport aux proportions contenus dans l'huile de soja sont respectivement de 15,75%, 0,89%, 7,22%, 12,05%, 8,27% et 21,35% (Oladiji et al, 2009).…”
Section: Valeurs Nutritionnellesunclassified
“…Cette huile selon Oladiji et al (2009) est plus riche en acides béhéniques, palmitoléiques, oléiques, gadoléiques, éruciques et 9, 12 éicosanoique que l'huile de soja. Le pourcentage d'élévation de ces gras par rapport aux proportions contenus dans l'huile de soja sont respectivement de 15,75%, 0,89%, 7,22%, 12,05%, 8,27% et 21,35% (Oladiji et al, 2009).…”
Section: Valeurs Nutritionnellesunclassified